CDK4/6 inhibitor treatment for patients with hormone receptor-positive, HER2-negative, advanced or metastatic breast cancer: a US Food and Drug Administration pooled analysis. Issue 2 (February 2020) - Gao, Jennifer J; Cheng, Joyce; Bloomquist, Erik; Sanchez, Jacquelyn; Wedam, Suparna B; Singh, Harpreet; Amiri-Kordestani, Laleh; Ibrahim, Amna; Sridhara, Rajeshwari; Goldberg, Kirsten B; Theoret, Marc R; Kluetz, Paul G; et al.
Summary: Background: Cyclin-dependent kinase 4/6 inhibitors (CDKIs) are indicated with endocrine therapy as first-line or second-line treatment for hormone receptor-positive, HER2-negative, advanced or metastatic breast cancer. We aimed to investigate the benefit of adding CDKIs to endocrine therapy in patients whose tumours might have differing degrees of endocrine sensitivity. Methods: We pooled individual patient data from all phase 3 randomised breast cancer trials of CDKIs plus endocrine therapy submitted to the US Food and Drug Administration before Jan 1, 2019, in support of marketing applications. Our pooled analysis included all randomly assigned patients in these trials who received at least one dose of CDKI or placebo with endocrine therapy (an aromatase inhibitor [letrozole or anastrazole] or fulvestrant). We did prespecified subgroup analyses in patients with progesterone receptor-negative disease; patients with a disease-free interval of 12 months or less; patients with de-novo metastases, lobular histology, and bone-only disease; patients with visceral metastases; and patients aged up to 40 years. Patients who were not treated, who received tamoxifen as endocrine therapy, or who were treated with an aromatase inhibitor but who had received previous chemotherapy in the metastatic setting (not first-line) were excluded from our pooled analyses. All studies had a primary endpoint of investigator-assessed progression-free survival, defined as time from date of randomisation to the initial date of documented cancer progression or death, whichever occurred first. Median progression-free survival was estimated with Kaplan-Meier methods. Hazard ratios (HR) with 95% CIs for progression-free survival were estimated by means of Cox regression models. Findings: The seven studies meeting this study's inclusion criteria were done between Feb 22, 2013, and Nov 3, 2017, with a median duration of follow-up of 19·7 months (IQR 15·9–25·9). 4200 patients were included in the pooled analysis, of whom 1320 received an aromatase inhibitor plus a CDKI, 932 received placebo plus an aromatase inhibitor, 1296 received fulvestrant plus a CDKI, and 652 received fulvestrant plus placebo. Across all seven pooled trials, the difference in estimated median progression-free survival was 8·8 months in favour of CDKI plus endocrine therapy over placebo plus endocrine therapy (range across the trials 6·8–13·3 months; HR 0·59, 95% CI 0·54–0·64). Progression-free survival results favoured the CDKI group in all prespecified clinicopathological subgroups analysed, with similar HRs to that for the broader intended-use population. In first-line aromatase inhibitor-treated patients (n=2252), the median progression-free survival in the CDKI plus aromatase inhibitor group was 28·0 months (95% CI 25·3–29·1) versus 14·9 months (14·0–16·7) in the placebo plus aromatase inhibitor group (difference 13·1 months; range across the trials 13·0–13·3 months; HR 0·55, 95% CI 0·49–0·62). In first-line fulvestrant-treated patients (n=396), the median progression-free survival was 18·6 months (95% CI 14·8–23·5) in the placebo plus fulvestrant group and not estimable (22·4 to not estimable) in the CDKI plus fulvestrant group (difference not estimable; HR 0·58, 95% CI 0·42–0·80). In the patients treated with fulvestrant in the second-line setting and beyond (n=1552), the difference in estimated median progression-free survival between the CDKI plus fulvestrant group and the placebo plus fulvestrant group was 6·9 months in favour of the CDKI group (range across the trials 5·5–7·3 months; HR 0·56, 95% CI 0·49–0·64). Interpretation: Since the addition of CDKI to endocrine therapy seemed to benefit all clinicopathological subgroups of interest in this pooled analysis, further research is needed to identify patient subgroups for whom endocrine therapy alone might be appropriate for first-line or second-line treatment of hormone receptor-positive, HER2-negative metastatic breast cancer. Funding: None.